(untitled) (Bangladesh Journal of Botany, 2015)
Twelve different isolates of Fusarium spp. collected from wheat grown in Syria were analyzed using amplified fragment length polymorphism (AFLP) markers. AFLP analysis allowed differentiation between species on the basis of banding patterns. A total of 654 scorable DNA bands were scored, of which 296 (44.54 %) were polymorphic. UPGMA dendrogram, based on Nei’s genetic distances, showed that isolates formed three phylogenetic groups; one of them did not fall into clades correlated to the origin or colour of the isolate, which suggests a regional dispersal of these species. However, isolates belonging to F. culmorum and F. equiseti collected from north-west of Syria and ICARDA, respectively fell into two separate sub-clusters. The level of genetic variability detected within Fusarium isolates by AFLP analysis confirmed that it is a reliable, efficient, and effective marker technology for determining genetic relationships in Fusarium spp. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21674 Bangladesh J. Bot. 43(2): 207-212, 2014 (September)